Method for More Successful Usage of Airbnb by Hosts and Guests in Developing Countries - Rajkovska, Mihaela; Santa, Mijalche (University of Maribor Press, 2022)
In this paper we aim to propose a method for more successful usage of Airbnb platform by the hosts and guests in North Macedonia. To achieve this, we have performed qualitative research and interviewed twenty individuals. The collected data was analyzed through grounded theorizing. Based on the analysis we identified that the dimensions under which the hosts have most control and through which can impact the value perception of the guests is the bargaining power they have. To increase the bargaining power, we have identified steps that the hosts should follow. These proposals are empirically based and practically useful.
Keywords: Sharing economy; AirBnB usage challenges; Developing countries